2013
DOI: 10.1371/journal.pone.0053430
|View full text |Cite
|
Sign up to set email alerts
|

JunB Mediates Basal- and TGFβ1-Induced Smooth Muscle Cell Contractility

Abstract: Smooth muscle contraction is a dynamic process driven by acto-myosin interactions that are controlled by multiple regulatory proteins. Our studies have shown that members of the AP-1 transcription factor family control discrete behaviors of smooth muscle cells (SMC) such as growth, migration and fibrosis. However, the role of AP-1 in regulation of smooth muscle contractility is incompletely understood. In this study we show that the AP-1 family member JunB regulates contractility in visceral SMC by altering ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…RhoA is the small GTPase activator of actin stabilizing kinase, ROCK1, which is the calcium independent activator of myosin regulatory light chain [26]. Myosin regulatory light chain stimulates NM IIA activity and promotes actin filament sliding, including ASMA [27]. …”
Section: Discussionmentioning
confidence: 99%
“…RhoA is the small GTPase activator of actin stabilizing kinase, ROCK1, which is the calcium independent activator of myosin regulatory light chain [26]. Myosin regulatory light chain stimulates NM IIA activity and promotes actin filament sliding, including ASMA [27]. …”
Section: Discussionmentioning
confidence: 99%
“…31 In addition, AP-1 has been implicated in the regulation of smooth muscle contractility through effects on both myosin and the actin cytoskeleton. 32 We found that the activation of c-Jun induced by TGF-b in HTFs was inhibited by ATRA, with this effect also likely contributing to the inhibition by ATRA of HTF contractility.…”
Section: Discussionmentioning
confidence: 63%
“…3,36 It has been described that HS intake increases endothelial production of TGF-β1, which can act in a paracrine fashion on the vessel wall participating in VSMCs differentiation toward a contractile phenotype. 18,[37][38][39] Here, we showed that in the vasculature of the sik1 −/− mice the HS intake increased TGF-β1 expression and downstream phospho-SMAD2/3 signaling compared with the wild-type mice, which suggests that the contractile phenotype of VSMCs should be favored in the sik1 −/− mice. Indeed, we found increased expression of contractile genes and of EN1 in the knockout compared with the wild-type mice aortas, only during HS intake.…”
Section: Discussionmentioning
confidence: 63%